Okwui Enwezor 2023 - Kültürhane: Hope in the Age of Compost (Okwui Enwezor Distinguished Lecture, 2024)
For the third time, the Cluster of Excellence organised the Okwui Enwezor Distinguished Lecture in July 2023. Established in the memory of late art curator Okwui Enwezor, each year the lecture series presents a prominent artist, curator, or scholar who engages with ground-breaking contributions to the rethinking of arts in a global perspective. On July 19 2023, the Okwui enwzeor distinguished Lecture featured the founders of Kültürhane, an activist community in Turkey. The lecture was entitled "Hope in the Age of Compost"